2000
DOI: 10.1073/pnas.200121897
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable species diversity in Malagasy mouse lemurs (primates, Microcebus )

Abstract: Phylogenetic analysis of mtDNA sequence data confirms the observation that species diversity in the world's smallest living primate (genus Microcebus) has been greatly underestimated. The description of three species new to science, and the resurrection of two others from synonymy, has been justified on morphological grounds and is supported by evidence of reproductive isolation in sympatry. This taxonomic revision doubles the number of recognized mouse lemur species. The molecular data and phylogenetic analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
188
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 219 publications
(201 citation statements)
references
References 42 publications
12
188
1
Order By: Relevance
“…Nonetheless, Yoder et al 31,32 have reported molecular evidence supporting the notion that all of the species recognized by Rasoloarison, et al 30 represent reproductively isolated entities.…”
Section: Genus Microcebusmentioning
confidence: 93%
See 1 more Smart Citation
“…Nonetheless, Yoder et al 31,32 have reported molecular evidence supporting the notion that all of the species recognized by Rasoloarison, et al 30 represent reproductively isolated entities.…”
Section: Genus Microcebusmentioning
confidence: 93%
“…Four of their recognized species, M. tavaratra, M. sambiranensis, M. ravelobensis, and M. berthae, were reported only from a single locality or from closely grouped localities, while the others, based on the data presented by Rasoloarison, et al 30 and by Yoder et al 31 have wider distributions. M. murinus occurs from Berenty in the far south, potentially as far north as the Sambirano, and more certainly to Kirindy; M. griseorufus from Berenty north and west toward Morombe; and M. myoxinus from the Tsiribihina River north, possibly as far as Soalala.…”
Section: Genus Microcebusmentioning
confidence: 96%
“…These category definitions are not restricted to amphibians. In Madagascar and elsewhere, molecular data have been used to detect unexpected levels of cryptic diversity in other animal groups (32,33,(41)(42)(43), and in many cases the biological identity of the previously undescribed genealogical lineages remains largely unassessed. Our definition of CCS (Table 1) relies on genetic divergence combined with a distinct difference in either morphology or in a character that mediates premating isolation (advertisement calls in frogs).…”
Section: Deep Conspecific Lineage (Dcl)mentioning
confidence: 99%
“…The global distribution of four vertebrate species is restricted to the forested areas between the Morondava and Tsiribihina rivers, with the last remaining population of the giant jumping rat (Hypogeomys antimena), the largest living endemic rodent of Madagascar (Sommer et al 2002;Young et al 2008); the only population of Madame Berthe's mouse lemur (Microcebus berthae), the smallest primate of the world Yoder et al 2000); the flattailed tortoise (Pyxis planicauda; Tidd et al 2001); and a frog (Aglyptodactylus laticeps; Glaw et al 1998;Glos et al 2008). Sixteen other vertebrate species with extremely restricted ranges are found in the KAFC including the striped mongoose (Mungotictis decemlineata; Razafimanantsoa 2003) and the white-breasted mesite (Mesitornis variegata; Durbin et al 2005; reviewed by Goodman and Raselimanana 2008).…”
Section: Introductionmentioning
confidence: 99%